(untitled) (Dermatology Reports, 2022)
We report the case of a 23-year-old woman with an erythematous, crusted patch of the scalp, lacking pustular lesions, with partial hair loss, developed after mechanical scalp trauma. Histopathological examination showed a dermal infiltrate, predominantly peri-adnexal and peri-vascular, rich in plasma cells and lymphocytes, but lacking neutrophils, possibly as a consequence of the time elapsed since the onset of the skin disease. Reduction of functional hair follicles was evidenced. Stains for bacterial or fungal infections were negative. Direct immunofluorescence was negative. Erosive pustular dermatosis of the scalp was diagnosed on the basis of clinical-anamnestic findings, supported by histology. Topical clobetasol propionate led to clinical improvement after a couple of weeks. Erosive pustular dermatosis of the scalp was diagnosed and soon after the patient developed also multiple sclerosis. Up to date, the pathogenesis of erosive pustular dermatosis of the scalp remains unknown, though a possible role of immunosenescence and autoimmunity has been suggested. Indeed, high levels of neutrophil-stimulating cytokines and chemokines have been found in erosive pustular dermatosis patients, possibly causing activation of an aberrant systemic neutrophilic reaction. Furthermore, the role of neutrophils has been recently highlighted also in the pathogenesis of multiple sclerosis. Herein we hypothesize a possible common immunological etiology of multiple sclerosis and erosive pustular dermatosis of the scalp, conceivably involving a hyperactivation of neutrophils.